Hubble Space Telescope hot Jupiter transmission spectral survey: a detection of Na and strong optical absorption in HAT-P-1b - Nikolov, N; Sing, D; Pont, F; Burrows, A; Fortney, J; Ballester, G; Evans, T; Huitson, C; Wakeford, H; Wilson, P; Aigrain, S; Deming, D; et al. (2014)
We present an optical to near-infrared transmission spectrum of the hot JupiterHAT-P-1b, based on Hubble Space Telescope observations, covering the spectral regime from 0.29 to 1.027μm with Space Telescope Imaging Spectrograph (STIS), which is coupled with a recent Wide Field Camera 3 (WFC3) transit (1.087 to 1.687μm). We derive refined physical parameters of the HAT-P-1 system, including an improved orbital ephemeris. The transmission spectrum shows a strong absorption signature shortward of 0.55μm, with a strong blueward slope into the near-ultraviolet. We detect atmospheric sodium absorption at a 3.3σ significance level, but find no evidence for the potassium feature. The red data imply a marginally flat spectrum with a tentative absorption enhancement at wavelength longer than ~0.85μm. The STIS and WFC3 spectra differ significantly in absolute radius level (4.3 ± 1.6 pressure scaleheights), implying strong optical absorption in the atmosphere of HAT-P-1b. The optical to near-infrared difference cannot be explained by stellar activity, as simultaneous stellar activity monitoring of the G0V HAT-P-1b host star and its identical companion show no significant activity that could explain the result. We compare the complete STIS and WFC3 transmission spectrum with theoretical atmospheric models which include haze, sodium and an extra optical absorber. We find that both an optical absorber and a supersolar sodium to water abundance ratio might be a scenario explaining the HAT-P-1b observations. Our results suggest that strong optical absorbers may be a dominant atmospheric feature in some hot Jupiter exoplanets. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.